Days Alive and Out of Hospital as an Outcome Measure in Patients Receiving Hyperacute Stroke Intervention - Joseph Donnelly; Jae Beom Hong; Luke Boyle; Vivien TY Yong; William K. Diprose; Juliette Meyer; Douglas Campbell; P. Alan Barber (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Patient outcome after stroke is frequently assessed with clinical scales such as the modified Rankin Scale score (mRS). Days alive and out of hospital at 90 days (DAOH‐90), which measures survival, time spent in hospital or rehabilitation settings, readmission and institutionalization, is an objective outcome measure that can be obtained from large administrative data sets without the need for patient contact. We aimed to assess the comparability of DAOH with mRS and its relationship with other prognostic variables after acute stroke reperfusion therapy. Methods and Results Consecutive patients with ischemic stroke treated with intravenous thrombolysis or endovascular thrombectomy were analyzed. DAOH‐90 was calculated from a national minimum data set, a mandatory nationwide administrative database. mRS score at day 90 (mRS‐90) was assessed with in‐person or telephone interviews. The study included 1278 patients with ischemic stroke (714 male, median age 70 [59–79], median National Institutes of Health Stroke Scale score 14 [9–20]). Median DAOH‐90 was 71 [29–84] and median mRS‐90 score was 3 [2–5]. DAOH‐90 was correlated with admission National Institutes of Health Stroke Scale score (Spearman rho −0.44, P<0.001) and Alberta Stroke Program Early CT [Computed Tomography] Score (Spearman rho 0.24, P<0.001). There was a strong association between mRS‐90 and DAOH‐90 (Spearman rho correlation −0.79, P<0.001). Area under receiver operating curve for predicting mRS score >0 was 0.86 (95% CI, 0.84–0.88), mRS score >1 was 0.88 (95% CI, 0.86–0.90) and mRS score >2 was 0.90 (95% CI, 0.89–0.92). Conclusions In patients with stroke treated with reperfusion therapies, DAOH‐90 shows reasonable comparability to the more established outcome measure of mRS‐90. DAOH‐90 can be readily obtained from administrative databases and therefore has the potential to be used in large‐scale clinical trials and comparative effectiveness studies.